BUDGETARY GOAL CHARACTERISTICS, AKUNTABILITAS, DAN TRANSPARANSI TERHADAP KINERJA ANGGARAN DIMODERASI KOMITMEN ORGANISASI - Hayyin Rizki Utami; Tantina Haryati (Jambura Economic Education Journal, 2023)
The complexity of regional financial management with minimal human resources when measured from the quality aspect, it is important to study the implementation of budgetary goal characteristics, transparency, and accountability in managing budget performance with the concept of value for money in government agencies. This study examines and analyzes the relationship between budgetary goal characteristics, transparency, and accountability for budget performance with the concept of value for money and organizational commitment as a moderating variable. This study used a quantitative method with the subject of employee/staff analysis related to the budget at the BPKPD Pamekasan Regency. The WarpPLS 7.0 application is used as a data analysis technique. The research findings show that budgetary goal characteristics, accountability, and transparency have a positive and significant effect on the value for money concept of budget performance management in the BPKPD, Pamekasan Regency. Organizational commitment can moderate budgetary goal characteristics, accountability, and transparency of budget performance management with a value for money concept.